(Hydroxy)apatite on cement: insights into a new surface treatment. Issue 19 (8th September 2021) - Turner, Ronald J.; Bots, Pieter; Richardson, Alan; Bingham, Paul A.; Scrimshire, Alex; Brown, Andrew; S'Ari, Mark; Harrington, John; Cumberland, Susan A.; Renshaw, Joanna C.; Baker, Matthew J.; Edwards, Paul R.; et al.
Abstract : We have developed a conceptual model describing the formation and mineralisation processes of hydroxyapatite during biogenic and abiotic treatment on cement surfaces. Abstract : (Hydroxy)apatite (HAp) [Ca10 (PO4 )6 (OH)2 ], has emerging potential as a cement coating material, with applications in environmental remediation, nuclear waste storage and architectural preservation. In these low temperature environments and when precipitating from aqueous solution on to a porous substrate, the crystal size, nucleation sites and modified surface properties created are key to designing the most effective coating. In this study we show that bacterial (biogenic) or chemical (abiotic) syntheses on to Portland cement alter these critical performance parameters. We identify that the most significant difference between these two methods is the rate of pH change of the solution during synthesis, as this alters the surface properties and layer structure of HAp formed on cement. We show that iron present in Portland cement is not incorporated into the HAp structure; that formation of nanoparticulate/nanocrystalline HAp begins in the top 20–50 μm of the cement pore structure; and that a slow pH rise in the deposition solution controlled by bacteria metabolic activity leads to a rougher and more hydrophilic HAp coating compared to the abiotic synthesis. The results present the possibility of tailoring the surface topography and hydrophilicity of (hydroxy)apatite coated cement.